IMPLEMENTATION OF MARKETING MANAGEMENT STRATEGY IN IMPROVING THE QUALITY OF ENGLISH LANGUAGE TEACHING IN HIGHER EDUCATION - Pratiwi, Yosi Mulyana; Khoiruman, Muhamad Alfi (Jurnal Review Pendidikan dan Pengajaran, 2025)
The increasing competition among higher education institutions has led to the growing importance of marketing management strategies in enhancing the quality of English language teaching. This study examines the implementation of marketing strategies, including branding, curriculum innovation, stakeholder engagement, and digital marketing, to improve student enrollment and learning outcomes. Using a qualitative research approach, data were collected through interviews with institutional leaders, faculty members, and students, as well as classroom observations. Thematic analysis was employed to identify key patterns and relationships in the data. The findings reveal that institutions with strong branding strategies, innovative and industry-aligned curricula, and active engagement with stakeholders through digital platforms and industry collaborations experience higher student satisfaction and program effectiveness. Additionally, technology-enhanced teaching methods, such as blended learning and AI-based assessment systems, contribute to improved language proficiency. The study concludes that a well-structured marketing management strategy is essential for increasing institutional visibility and enhancing the overall quality of English language education. It is recommended that universities invest in digital marketing, industry partnerships, and faculty development to maintain a competitive edge and better equip students with essential communication skills for global academic and professional success